2021
DOI: 10.3390/catal11080974
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Efficiency and Kinetics Analysis of an Advanced Oxidation Process Utilizing Ozone, Hydrogen Peroxide and Persulfate to Degrade the Dye Rhodamine B

Abstract: In this study, the effectiveness of a rhodamine B (RhB) dye degradation process at a concentration of 20 mg/L in different advanced oxidation processes—H2O2/UV, O3/UV and PDS/UV—has been studied. The use of UV in a photo-assisted ozonation process (O3/UV) proved to be the most effective method of RhB decolorization (90% after 30 min at dye concentration of 100 mg/L). The addition of sulfate radical precursors (sodium persulfate, PDS) to the reaction environment did not give satisfactory effects (17% after 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…At a higher concentration, the substrate absorbs more photons thereby decreasing the photons available for ZnO activation. The substrate molecules are in excess in relation to the available active sites at very high concentrations (Zawadzki et al, 2021 ). They are a lot more compared to the generated ROS as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a higher concentration, the substrate absorbs more photons thereby decreasing the photons available for ZnO activation. The substrate molecules are in excess in relation to the available active sites at very high concentrations (Zawadzki et al, 2021 ). They are a lot more compared to the generated ROS as well.…”
Section: Resultsmentioning
confidence: 99%
“…Any additional increase in substrate concentration cannot produce correspondingly more ROS or other reactive free radicals once it has filled all the active sites on the catalyst and interacted with the available free radicals. The production of surface-initiated reactive free radicals is suppressed by the reactant, intermediaries, and/or products that completely dominate the catalytic surface (Zawadzki et al, 2021 ). At any point in time, there will be an optimum for the maximum number of substrate molecules to interact with the reactive free radicals formed by the surface.…”
Section: Resultsmentioning
confidence: 99%
“…According to the theory of mass transfer, increasing the concentration of ozone entering the reaction media increases the concentration of dissolved ozone in the environment, and since ozone has a dual role as a producer of hydroxyl oxidizing radicals from the reaction with hydrogen peroxide and direct oxidation by itself. So increasing the concentration of ozone increases the efficiency of the process 46 . A study conducted by Wang and her colleagues on the decolorization of acid orange 2 indicated that increasing the ozone flow rate from 35 to 118 mg/L increased the removal efficiency from 80 to 98 percent 47 .…”
Section: Resultsmentioning
confidence: 99%
“…This is because oxidants offer distinct advantages within AOPs. Briefly, advantages of AOPs-based hydrogen peroxide and persulfate include efficient decomposition of a wide range of pollutants (especially refractory pollutants), generation of non-selective and selective oxidizing species (hydroxyl and persulfate radicals), flexibility in operation, low-cost and production of lower damaging by-products, accessibility and possibility for large-scale treatment applications [ [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%